System identification of unmanned aerial vehicles - Carnduff, S. D. (Cranfield University, 2008)
The aim of this research is to examine aspects of system identification for unmanned aerial vehicles (UAVs). The process for aircraft in general can be broken down into a number of steps, including manoeuvre design, instrumentation requirements, parameter estimation, model structure determination and data compatibility analysis. Each of these steps is reviewed and potential issues that could be encountered when analysing UAV data are identified. Problems which may be of concern include lack of space within the airframe to mount sensors and a greater susceptibility to the effects of turbulence in comparison to manned aircraft. These issues are investigated using measurements from two experimental sources. Firstly, Cranfield University’s dynamic wind tunnel facility is utilised, in which scale models are flown in semi-free flight. The control surfaces are actuated so that inputs, similar to those used when flight testing full-sized aircraft, can be applied and the resultant response of the model is recorded. Measurements from a 1/12 scale model of the BAe Hawk and a 1/3 scale model of the FLAVIIR project demonstrator UAV are used. An added benefit of the facility to this work is that the wind tunnel models are comparable in size to the miniature class of UAVs. Therefore, practical issues, similar to those faced for these aircraft, are encountered with the wind tunnel experiments. The second source of experimental data is UAV flight test data supplied by BAE Systems.